Pengembangan E-Modul Discon Berbasis Android (E-Modul Disroid) Materi Bunyi bagi Siswa Sekolah Dasar - Dewi Pendit, Sinta Satria; Amelia, Chairunnisa; Azizah, Azizah; Pilok, Nurnila A.; Sitepu, Melyani Sari (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The online learning process is not effective because the media used in the science learning process is limited to books and Whatapps Group applications. This study aims to develop learning media (module) based on android on sound material for students IV SD. This research is a research and Development with the ADDIE model, which consists of five stages, namely, Analyze, Design, Development, Implement, and Evaluation. The population in this study are fourth-grade students of SDN 8 Mambo. The research instrument used a media validation questionnaire sheet, material validation, and user questionnaire (teachers and students). Data analysis using descriptive analysis techniques. Based on the results of the data analysis obtained, the validity value of the material from the aspect of self-instruction of 87.6% category is very valid, the self-contained aspect of 91.7% category is very valid, stand-alone aspect of 91.7% category is very valid, adaptive aspect of 83.3% category is valid, and user-friendly aspect of 100% category is very valid. The validity of the media on indicators of system quality and information quality with a value of 100% is a very valid category. The user practicality sheet obtained a value of 77.9% with the practical type. So it can be concluded that the Android-based e-module (E-module DISROID) developed in the criteria is very valid and very practical so that this module can be used in science learning, especially for practicum activities in elementary school Class IV.